Gambaran Kedisiplinan Peserta Didik Kelas VIII di MTs Negeri 4 Bogor - Repina Aulia; Asep Samsudin; Siti Fatimah (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2023)
Discipline is an attitude of obedience and obedience to the rules or regulations that apply with full responsibility without any coercion from anyone. This study aims to determine the description of student discipline at MTs Negeri 4 Bogor. The approach used in this study is a qualitative approach with a descriptive method. Data collection techniques used in this study were observation, interviews and documentation. The results showed that the low discipline of students against the rules at school was caused by a lack of awareness of discipline, not being able to control their own will, managing themselves and a lack of attention from parents to motivate and remind them to be orderly, so they do whatever they want.